Literature review: nutrition supplementation for muscle fatigue in athletes - Mardiana, Mardiana; Kartini, Apoina; Sutiningsih, Dwi; Suroto, Suroto; Muhtar, Muhammad Solihuddin (Jurnal Keolahragaan, 2023)
The use of natural or conventional-based supplementation has become a popular strategy among athletes seeking to reduce oxidative stress, improve recovery, and enhance athletic performance. This literature review searched four reputable international electronic databases, including PubMed, MedRxiv, Cochrane, and Clinical Trial.gov until December 2021, using Boolean operators with keywords and Mesh methods. The keywords used were "Supplementation", AND "Muscle Fatigue Recovery", AND "Athletes", which yielded 24 articles as study findings. The literature review found that exhaustive exercise can induce a neutrophil antioxidant response by increasing antioxidant enzymes. Nutritional supplements, specifically antioxidant supplements, Branched Chain Amino Acid (BCAA), citrulline, omega-3, and caffeine, have been scientifically proven to reduce oxidative damage, which can block signaling pathways related to muscle hypertrophy. In order to combat muscle fatigue in athletes based on this research (literature review), natural ingredients and synthetic nutritional supplements have been utilized as dietary interventions. This literature review identified numerous natural micronutrients and synthetic supplements used in sports that possess anti-fatigue properties, decrease oxidative stress and enhance athletes' endurance capacity. The effectiveness of nutritional supplements in addressing muscle fatigue may vary based on the various ingredients in the supplements. However, natural-based supplements have become a preferred option among athletes and coaches currently.